Principios de las operaciones de mantenimiento de la paz (2011)
This article is part of a research project aimed at performing an analysis of what is usually called “the factual nature of the normativity” on the one hand, and “the normative character of the factual” on the other side, from the perspective of different branches of public law: constitutional law, public international law, history of law and administrative law. This analysis is intended to provide theoretical and practical references regarding the relation of Law with society and politics, and their reciprocal and continuous influence. The juridical problem addressed in the overall research project is analyzing, studying and understanding the relationship between social and political movements, with the creation and interpretation of law in Colombia and all over the world (understood as the relations derived from public international law).